ANALYSIS OF WORK POSTURE IN EMBROIDERY MACHINE OPERATORS USING THE REBA AND OWAS METHODS AT PT XYZ - Idam Aqmul Fatik; Yanuar Pandu Negoro; Purwanto Purwanto (INTECOMS: Journal of Information Technology and Computer Science, 2025)
Ergonomics plays a crucial role in health, significantly influencing worker welfare. Neglecting occupational health and safety can harm both employees and companies. PT XYZ, a producer of Muslim clothing, still involves manual activities in its production, which pose risks such as workplace accidents, especially during manual material handling (MMH). Small-scale industrial work exposes workers to various hazards, including Musculoskeletal Disorders (MSDs). This study aims to identify workers' postures using the REBA and OWAS methods. The REBA score is 7, while the OWAS score is 2, indicating the need for intervention. Consequently, ergonomic chairs are being designed for workers to improve their work environment principles. Keywords : Reba, Owas, Ergonomi, Musculoskeletal disorders